Caracterização ótica de poços quânticos de GaMnAs - Holgado, Danny Pilar Araucano (2007)
In this work, we have studied GaAs/AlAs/Ga1-xMnxAs quantum wells (QWs) with low Mn concentration ( 0 < x < 0,2%). The samples were grown by Molecular Beam Epitaxy (MBE) in high temperature (450 C). The growth conditions were chosen to reduce the incorporation of As and interstitial Mn resulting in samples of good optical quality. We have studied samples growth in (311B) and (001) GaAs substrates with different manganese concentrations, x = 0.0%, 0.07%; 0.1%;. We have performed measurements of polarized resolved photoluminescence for magnetic field up to 15T in Faraday configuration. We determined the degree of circular polarization and the excitonic spin-splitting for the QW emission as function of magnetic field.